The Effect of MSME DTP Final PPh Incentives on the Sustainability of MSMEs in the Covid-19 Pandemic Period: Case Study of MSMEs that register with one of the KPP in the City of Bandung - Jihan Ayu Lestari; Ignatius Oki Dewa Brata (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The spread of the Covid-19 Pandemic that hit Indonesia at the end of 2019 caused a downturn in various sectors, especially the economic sector, including MSME players, who experienced a significant decrease in turnover. In order to maintain stability and restore the national economy, the government issued a tax incentive policy (PMK Number 82/PMK.03/2021) to continue to support MSME productivity during the Pandemic. This study aims to determine how much influence the Government-borne Final Income Tax Incentives (DTP) given to MSME actors on the sustainability of MSMEs registered at one of the Primary KPPs in Bandung City during the Covid-19 Pandemic. The method used in this research is explanatory research with a quantitative approach. The data used uses primary data in the form of a questionnaire addressed to taxpayers of MSME actors registered at one of the KPP Pratama in Bandung, which 35 respondents fill in. The study results show a significance value (Sig.) of 0.046 <0.05 in the T-Test test, so the researchers concluded that the DTP Final Income Tax Incentive positively affected the sustainability of MSMEs during the Covid-19 Pandemic. The simple linear regression equation formed is Y = 16.480 + 0.387X with a coefficient of determination of 0.115 (11.5%). This condition means that the dependent variable DTP Final Income Tax Incentive has the ability of 11.5% in explaining the variance on the sustainability of MSMEs, and there is still 88.5% of the variance explained by other independent variable factors. Therefore, it is necessary to have other independent variables, such as Tax Rates, Tax Socialization, and Financial Conditions, to affect the sustainability of MSMEs during the co-19 Pandemic simultaneously.